Effect-based assessment of passive air samples from four countries in Eastern Europe - Érseková, Anita; Hilscherová, Klára; Klánová, Jana; Giesy, John P; Novák, Jiří (Environmental monitoring and assessment, 2014)
Although passive sampling has been previously used for the monitoring of volatile and semi-volatile contaminants in air, there are limited data on the use of this technique coupled with bioassays based on specific biological responses. Biological responses including those mediated by the aryl hydrocarbon (AhR) receptor as well as (anti-)estrogenicity and (anti-)androgenicity of samples from four Eastern European countries (Lithuania, Slovakia, Romania, and Serbia) were determined. To address the potential differences of specific toxic potencies of pollutant mixtures in ambient air in Eastern Europe, each country was characterized by a single more remote location that served to determine regional background conditions and one location in more urbanized and industrialized locations, which were defined as "impacted" areas. Besides samples from Lithuania, a significant gradient in concentrations of AhR-mediated potency from background and impacted localities was observed. Greatest potencies were measured in samples from impacted locations in Romania and Slovakia. Concentrations of polycyclic aromatic hydrocarbons (PAHs) that were quantified accounted for 3-33 % of the 2,3,7,8-tetrachlorodibenzo-p-dioxin equivalents determined by use of the bioassay. No significant estrogenic potency was detected but anti-estrogenic effects were produced by air from two background locations (Lithuania, Slovakia) and three impacted locations (Lithuania, Romania, and Serbia). Anti-androgenic potency was observed in all samples. The greatest anti-estrogenic potency was observed at the background location in Slovakia. Anti-estrogenic and anti-androgenic potencies of studied air samples were probably associated with compounds that are not routinely monitored. The study documents suitability of passive air sampling for the assessment of specific toxic potencies of ambient air pollutants.
Keywords: Air Pollution; polycyklické aromatické uhlovodíky; Europe, Eastern; látky znečišťující vzduch; východní Evropa; Polycyclic Aromatic Hydrocarbons; polychlorované dibenzodioxiny; receptory aromatických uhlovodíků; Environmental Monitoring; znečištění ovzduší; Estrogens; Air Pollutants; monitorování životního prostředí; Receptors, Aryl Hydrocarbon; Polychlorinated Dibenzodioxins; estrogeny